2016
DOI: 10.1089/jpm.2015.0240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inpatient Palliative Care on Treatment Intensity for Patients with Serious Illness

Abstract: Hospital-based palliative care programs alone may not be sufficient to impact ICU LOS or hospice length of enrollment for all chronically ill older adults admitted to hospitals. Future work should measure hospital-wide palliative care outcomes and effects of core palliative knowledge and skills provided by nonpalliative care specialists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…In a retrospective study, Hua et al, found that patients in the intervention and control group experienced the same length of stay (6 days) but patients in the intervention group were 46% more likely to be discharged to a hospice [76]. These findings are supported by those of Horton et al [77].…”
Section: A; Innovations Supporting Early Hospital Dischargementioning
confidence: 83%
See 2 more Smart Citations
“…In a retrospective study, Hua et al, found that patients in the intervention and control group experienced the same length of stay (6 days) but patients in the intervention group were 46% more likely to be discharged to a hospice [76]. These findings are supported by those of Horton et al [77].…”
Section: A; Innovations Supporting Early Hospital Dischargementioning
confidence: 83%
“…A total of 1252 abstracts were reviewed by one author, resulting in the identification of ten categories of initiatives grouped under three broad headings (Fig. 1, Table 1): 1;'Facilitating entry into the hospice and community care system' [27], 2a-2 g; 'Preventing admission' and 3a&3b; 'Facilitating discharge' (Table 1) [56,66,72,[75][76][77][78]. Classification was reviewed by a second author.…”
Section: Partmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study, Hua et al, found that patients in the intervention and control group experienced the same length of stay (six days) but patients in the intervention group were 46% more likely to be discharged to a hospice (76). These findings are supported by those of Horton et al (77).…”
Section: A; Innovations Supporting Early Hospital Dischargementioning
confidence: 83%
“…'Facilitating discharge' (Table 1) (56,66,72,(75)(76)(77)(78). Classification was reviewed by a second author.…”
Section: Partmentioning
confidence: 99%